An Evaluation of Policy Measures against Global Warming by Promoting Effective Use of Potential Energy in Wastes - Susumu Uchida; Yoshiro Higano (European Regional Science Association (ERSA), 2005)
Utilizing potential energy in wastes is significant for achieving sustainable development of the environment and the society. It can not only prevent the wastes from polluting the environment, but also possess many other advantages such as saving energy resources, material recycle and creation of employment. Moreover, reuse of wastes can also play an important role in mitigating global warming by reducing emission of methane, which is likely to be generated from stockbreeding wastes left in the open. The greenhouse effect of a methane molecule is 21 times higher than that of a carbon dioxide. To promote effective use of potential energy in wastes and restructuring the existing energy system, some management instruments and economic policies need to be adopted. In this regard, levying tax on emission of greenhouse gases (GHGs) and subsiding industries producing energy from wastes are considered most applicable and effective. The aim of this study is to evaluate Japanese economic policies in which the tax and subsidy are introduced. For this purpose, a socioeconomic model has been constructed. The model is based on an I/O model and considers the flow of wastes and energy. New industries which produce energy from wastes, as well as the economic policies of the tax and the subsidy are introduced in the model. Being subject to restriction on total emission of GHGs, GDP is maximized as the objective function.The effects of the policies on reducing GHG emission and promoting new industries have been analyzed and the optimum tax rate is proposed.
Keywords: 330